Coupling lactic acid fermentation of food waste at various concentrations as storage strategy with dark fermentation for biohydrogen production - Roslan E.; Mohamed H.; Abu Hassan S.H.; Carrere H.; Trably E. (Elsevier Ltd, 2025)
Lactic acid fermentation (LAF) has recently been considered a promising strategy to store food waste (FW) prior to dark fermentation (DF), as it can stabilize organic matter with no negative impact on biohydrogen potential (BHP). However, concentrations can affect LAF and its subsequent impact on BHP is not known. This novel study evaluates the impact of storing FW by LAF at 1%, 5%, 10%, 15% and 20% total solids (TS), at 35 C and 23 C, subsequently converted to biohydrogen through DF. Storing FW in LAF at 5%, 10%, 15% and 20% TS has no impact on its BHP (88 23 mL/gVS). Storing at 1% TS increases variability of metabolic pathways, with replicates undergoing butyric fermentation instead of LAF, resulting in 33 mL/gVS and 13 mL/gVS of BHP, compared to the total average of all conditions at 84 25 mL/gVS. Microbial analysis shows Lactobacillus sp. and Weissella sp. as the main genera selected during storage. The concentrations affect the relative abundance of various remaining genera, such as Burkholderia-Paraburkholderia sp. at 20% TS and Lactococcus sp. at 1% TS. Except at low TS, LAF is a robust storage strategy of FW prior to DF, preserving its BHP without the need for conventional refrigeration. ? 2024 Hydrogen Energy Publications LLC